2009
DOI: 10.1007/s00066-009-1982-z
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Hypofractionated and Conventionally Fractionated Three-Dimensional External-Beam Radiotherapy for Localized Prostate Adenocarcinoma

Abstract: In this first evaluation, the HFRT schedule is feasible and induces acceptable or even lower acute toxicity compared with the toxicities in the CFRT schedule. Extended follow-up is needed to justify this fractionation schedule's safety in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 25 publications
(22 reference statements)
1
21
0
Order By: Relevance
“…Whereas the first analysis of the RTOG 9413 trial reported a benefit of whole-pelvis (WP) irradiation [42], this was unclear with longer follow-up [28] and the French GETUG-01 trial showed no difference between prostate-only (PO) and WP irradiation [41]; however, toxicity was increased with WP irradiation. There is now strong evidence for a low α/β value of prostate cancer [33], lower compared to late rectal toxicity [9], and clinical results support the use hypofractionated irradiation schemas [3,27,34,49].Escalation of the irradiation doses, WP irradiation and hypofractionated schemas all bear the risk of increased toxicity. Consequently, conformal treatment planning and precise treatment delivery are required for achieving an acceptable therapeutic ratio.…”
mentioning
confidence: 98%
“…Whereas the first analysis of the RTOG 9413 trial reported a benefit of whole-pelvis (WP) irradiation [42], this was unclear with longer follow-up [28] and the French GETUG-01 trial showed no difference between prostate-only (PO) and WP irradiation [41]; however, toxicity was increased with WP irradiation. There is now strong evidence for a low α/β value of prostate cancer [33], lower compared to late rectal toxicity [9], and clinical results support the use hypofractionated irradiation schemas [3,27,34,49].Escalation of the irradiation doses, WP irradiation and hypofractionated schemas all bear the risk of increased toxicity. Consequently, conformal treatment planning and precise treatment delivery are required for achieving an acceptable therapeutic ratio.…”
mentioning
confidence: 98%
“…Moreover, as shown in a recent report, great care must be taken to avoid late effects such as duodenal ulceration [38] and technical details such as respiratory motion control methods gain high importance in hypofractionated schedules. Even if reported acute toxicities can be lower with hypofractionated schedules [38,47], the opposite can be true for late toxicities.…”
Section: Future Perspectives In External Beam Radiotherapy (Ebrt) Formentioning
confidence: 94%
“…Although long-term results from Canadian [37] and Australian [38] trials are available, the doses and radiation techniques used in these studies do not reflect current clinical practice. Trials with higher doses and modern techniques have already published preliminary findings [39][40][41][42][43]. However, we are still awaiting for their data to mature.…”
Section: Five-year Viewmentioning
confidence: 97%
“…There was a small but significant increase in acute �I toxicity in the hypofractionation arm between weeks 2 and 4, but otherwise no significant difference for other acute morbidity. Also, an article from Lithuania by Norkus et al reported the preliminary results of 91 patients randomly assigned between 74 �y in Review 37 fractions (conventional fractionation arm) and 57 �y in 17 fractions (hypofractionation arm) using a five-field 3D-conformal technique [40,41]. At 3 months, no grade 3 or 4 toxicities were noted.…”
Section: Phase III Trialsmentioning
confidence: 97%